PENGARUH PERENCANAAN DAN PERILAKU PEKERJA PROYEK TERHADAP IMPLEMENTASI K4 (KEAMANAN, KESELAMATAN, KESEHATAN DAN KEBERLANJUTAN) PADA PEKERJAAN APARTEMEN THE STATURE JAKARTA - Mujiman; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2023)
The number of work accidents and work-related diseases is very detrimental to many parties, especially the workforce concerned so of course the aspects of security, safety, health and sustainability (K4) have an important role so that accidents in the construction of construction projects can be prevented as early as possible so that unwanted things occur in construction work. The objectives of the problem in this study are (1) Does project planning affect K4 in apartment construction. (2) Does workers' knowledge affect K4 in apartment construction. (3) Do workers' attitudes affect K4 in apartment construction. (4) Do workers' actions affect K4 in apartment construction. This research methodology uses descriptive research with a quantitative approach. The number of samples involved in this study were 90 respondents / construction workers with 73 respondents as main contractors, 12 respondents as consultant planners and 5 respondents as project owners. The results of this study explain that planning affects K4 with a path coefficient value of 0.104. Worker's knowledge influences K4 with a path coefficient value of 0.215. Workers' attitudes influence K4 with a path coefficient value of 0.305. Workers' actions affect K4 with a path coefficient value of 0.404.